2015
DOI: 10.1016/j.ydbio.2015.03.025
|View full text |Cite
|
Sign up to set email alerts
|

Wnt/ß-catenin signaling is required for radial glial neurogenesis following spinal cord injury

Abstract: Spinal cord injury results in permanent sensorimotor loss in mammals, in part due to a lack of injury-induced neurogenesis. The regeneration of neurons depends upon resident neural progenitors, which in zebrafish persist throughout the central nervous system as radial glia. However the molecular mechanisms regulating spinal cord progenitors remain uncharacterized. Wnt/ß-catenin signaling is necessary for the regenerative response of multiple tissues in zebrafish as well as other vertebrates, but it is not know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
94
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(98 citation statements)
references
References 32 publications
4
94
0
Order By: Relevance
“…2c). These cells have previously been described as glial cells 14 .
Fig. 2Wnt/β-catenin signaling is mainly active in fibroblast-like cells after spinal cord lesion.
…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…2c). These cells have previously been described as glial cells 14 .
Fig. 2Wnt/β-catenin signaling is mainly active in fibroblast-like cells after spinal cord lesion.
…”
Section: Resultsmentioning
confidence: 90%
“…Moreover, axonal reconnection, which is necessary for functional recovery in adult 11 and larval zebrafish 12, 13 , also depends on Wnt/β-catenin pathway activity in both systems 14, 15 . Wnt/β-catenin signaling involves extracellular Wnt ligand-induced stabilization and translocation of β-catenin into the nucleus where it modifies target gene transcription together with Tcf/Lef family proteins 16 .…”
Section: Introductionmentioning
confidence: 99%
“…This low activity state could be regulated by extracellular or intracellular pathway antagonists, or radial glia might simply fail to express the appropriate receptors to transduce Wnt signals. Regardless of the mechanism, it appears that this characteristic of hypothalamic radial glia is similar to other radial glial populations in the zebrafish retina and spinal cord (Goldman, 2014;Briona et al, 2015), but differs from radial glia in the mammalian dentate gyrus (Qu et al, 2010). Other studies have similarly shown that neural progenitor populations vary dramatically in their interpretation of pathway activity (Poschl et al, 2013).…”
Section: Discussion Hypothalamic Radial Glia Exhibit Multiple Featurementioning
confidence: 92%
“…Muller glia are generally protective to RGCs (Chong and Martin, 2015), induce RGC neuritogenesis in vitro (Garcia et al, 2002), and viral delivery of CNTF to Muller glia promoted optic nerve axonal extension and sprouting (Pernet et al, 2013a). Therefore, it is possible that Muller glia play a supportive role to RGCs following Wnt stimulation that aids in survival and promotes regeneration, similar to its function in astroglia following spinal cord injury (Duncan et al, 2014, Briona et al, 2015). In contrast, amacrine cells are generally inhibitory to RGC regeneration (Goldberg et al, 2002, Chong and Martin, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Also, Wnt3a may directly regulate growth cone remodeling by altering microtubule stability through differential binding of its downstream components, APC and Dvl1, to the positive ends of microtubules (Purro et al, 2008). Wnt signaling has also been shown to promote axonal growth within the adult spinal cord and sensory neurons after injury (Liu et al, 2008, Hollis and Zou, 2012) (Yin et al, 2008, David et al, 2010), and Wnt signaling regulates astrogliosis and radial glial neurogenesis during axon regeneration following CNS injury (Duncan et al, 2014, Briona et al, 2015). Wnt signaling is known to regulate inflammatory signaling, which has reparative and pro-regenerative effects (Marchetti and Pluchino, 2013).…”
Section: Introductionmentioning
confidence: 99%